2005
DOI: 10.17221/5666-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy of complicated uterine stump pyometra in five bitches: a case report

Abstract: ABSTRACT:One of the severe complications of ovariohysterectomy is the incomplete removal of one or two ovaries, which is also known as ovarian remnant syndrome. This condition is usually followed by uterine stump pyometra, which can be described as the infection of uterine body tissue remaining after the operation. However, both conditions may also be encountered separately. In this study, the clinical findings, therapies and long term postoperative conditions of five ovarioectomized bitches with uterine stump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…It is possible that this is because of the much lower rate of intraoperative hemorrhage in our LOE than is reported with open OHE, perhaps because of improved observation of the ovary (provided by the laparoscope's magnification), or it may simply reflect improvements made in current technique. The interval from OHE to ORS can vary from 1 month to 4 years . Therefore, despite a median follow‐up time of 737 days, it is possible that we have underestimated the incidence of ORS as bitches may have shown signs after the period covered by this study.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that this is because of the much lower rate of intraoperative hemorrhage in our LOE than is reported with open OHE, perhaps because of improved observation of the ovary (provided by the laparoscope's magnification), or it may simply reflect improvements made in current technique. The interval from OHE to ORS can vary from 1 month to 4 years . Therefore, despite a median follow‐up time of 737 days, it is possible that we have underestimated the incidence of ORS as bitches may have shown signs after the period covered by this study.…”
Section: Discussionmentioning
confidence: 95%
“…The ORS is observed more rarely in cats than in dogs because of the deep abdominal cavity, more sturdy ligamentum suspensorum ovarii and obesity in dogs ( By the surface of the removed residual ovarian tissue, we can identify follicles or follicular cysts, with even a possible presence of corpora lutea and increased vascularisation (Pearson, 1973;Prats, 2001;Howe, 2006;Ball et al, 2010), which can lead to intrasurgical bleeding as a complication in the operation of the ORS (Sontas et al, 2007), which in our case was avoided. In 71% of cases, together with ORS, an uterine stump pyometra develops under hormonal influence, particularly of progesterone (Okkens et al, 1981;Musal and Tuna, 2005), which is reaffirmed by us with this cat. The uterine residue can develop purulent inflammation and cystic endometriosis.…”
Section: Aimmentioning
confidence: 54%
“…This may be due to a small abdominal wall incision that makes difficult to visualize, reach and carry out the ligature of the ovary or ovaries, or to incorrect ligaturing of ovarian tissues or anatomical location of the right ovary (Wallace, 1991, Miller, 1995, Johnston et al, 2001a, Prats, 2001, Sontas et al, 2007. Anatomically, the right ovary and uterine horn are located in a more cranial position than the left ovary and uterine horn and the I S S U E 2 , 2 0 1 7 suspensory ligament is shorter, making that ovary more difficult to exteriorize, which predisposes the surgeon to leave the ovary during the surgery (Evans andChristensen, 1993, Sontas et al, 2007 In the above and in another clinical report (Pearson, 1973;Okkens et al, 1981;Musal and Tuna, 2005) it was observed that in 58% and 71% of uterine stump pyometra cases there is also functional ovarian tissue present. This is considered important evidence of hormonal influence, especially progesterone secretion, which is essential in the formation of stump pyometra (Nelson and Feldman, 1986;Johnston et al, 2001a, Musal andTuna, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from the examination of the bitch in this case were consistent with the abovementioned findings. Musal and Tuna (2005) and Sontas et al (2010) reported cases of concomitant occurrence of ORS, TVT and stump pyometra in bitches. However, no uterine tissue was noted in the ultrasonographic exam and laparotomy in our patient.…”
Section: Discussionmentioning
confidence: 99%